P201 PURSUING COMPLETENESS OF CORONARY REVASCULARIZATION IN ACUTE SETTING: TIMING AND STRATEGIES. (18th May 2022) - Fazzini, L; Ricci, S; Angius, S; Cadeddu, M
Abstract: Patient Presentation: A 59 y/o male with history of arterial hypertension and allergic asthma was admitted to our Coronary Care Unit because he went to a spoke emergency department after complaining oppressive and not continuous chest pain for a couple of hours travelling up to the left arm. Increase in cardiac troponin and mild ST–elevation in D3 lead were found. At the spoke cardiology department was treated with intravenous nitrates with relief and Ticagrelor loading dose was administered. He underwent two coronary angiographies, the first one aimed to treat the culprit lesion and the second one to complete revascularization before discharge Management: A heart ultrasound (US) described normal left ventricle ejection fraction (LVEF) with some of the right coronary segments akinesis. The first coronary angiography showed eccentric stenosis (80%) of distal right coronary artery (RCA) with endoluminal thrombosis; intraluminal filling defect of the left main coronary artery (LMCA) which request Optical Coherence Tomography evaluation that showed plaque rupture and red thrombus of LMCA; chronic total occlusion of left anterior descending artery (LAD) with several stenosis up to the apical segments. Glycoprotein IIb/IIIa receptor antagonist infusion was started, and we've been forced to treat first the LMCA with drug–eluting stent and then the culprit lesion with angioplasty and two drug–eluting stents complicated by intrastent thrombosis treated with mechanic and rheolytic thrombectomy. Seven days later rotational atherectomy was performed due to LAD artery's severe calcifications complicated by LMCA intrastent thrombosis caused by stenting crush; cardiopulmonary arrest occurred. Impella ventricular assist device was placed. After LMCA stent optimization, one more drug–eluting stent was placed. Eight days later, heart US described LVEF 37% with apex and right coronary segments hypo–akinesis. Discussion: According to latest NSTEMI guidelines, a single stage pursuing of completeness revascularization on multiple vessel disease would have been the best option. In this case, completeness of revascularization hasn't been achievable due to LMCA plaque rupture. From a technical point of view, considering the complexity of the few days earlier treated LMCA lesion, proximal to LAD lesions we were going to treat, it would have been suitable waiting about four weeks to complete stent endothelization. By the way, it would have been out–guidelines approach.